Major and minor risk factors for postoperative abdominoplasty complications: A case series - Daronch, Oona Tomiê; Marcante, Renata Fernanda Ramos; Neto, Aristides Augusto Palhares (Elsevier, 2022)
Background: Although abdominoplasty is a safe and popular surgery, it is associated with a higher complication rate than other body contouring procedures. Therefore, identifying predictive factors of major and minor complications in patients who have undergone abdominoplasty is necessary to achieve better treatment outcomes after major weight loss. Methods: This retrospective study analyzed the medical records of patients who underwent abdominoplasty between January 2016 and December 2019. The inclusion criteria were patients aged >18 years who underwent abdominoplasty as the only surgical procedure and had adequate follow-up. Other patients were excluded from the study. Statistical evaluation was performed using SPSS 20.0; statistical significance was set at a P-value of <0.05. Results: The study included a total of 152 patients, of whom 146 (96.1%) were women and 6 (3.9%) were men. The mean patient age was 41.1 ​± ​9.8 years. Comorbidities were reported in 67 patients (44.07%). A direct proportional relationship was observed between the weight of the resected tissue and occurrence of general complications (P=0.01), and the presence of comorbidities increased the occurrence of minor (P=0.04) and major complications (P=0.01). Conclusion: Abdominoplasty is an aesthetic surgical plastic procedure, and its application has increased over the years. Despite its popularity, patient safety requires further attention due to the high risk of complications. It is essential to study all risk factors.
Keywords: Abdominoplasty; Major complications; Minor complications